The Inheritence System Sistem Kewarisan Keluarga Melayu-Tionghoa di Kabupaten Belitung Timur dalam Kerangka Pluralisme Hukum di Indonesia - Julianda; Diana Zuhroh (TERAJU: Jurnal Syariah dan Hukum, 2026)
This study aims to understand the inheritance system of Malay-Chinese families in East Belitung within the framework of legal pluralism in Indonesia. The phenomenon studied focuses on the dynamics of interaction between customary law, religious law and state law in inheritance practices amongst multi-ethnic communities living side by side socially and culturally. Using a normative-empirical qualitative approach, this study explores and examines which inheritance laws are specifically used in multicultural communities in Indonesia. Data was collected with , through semi-structured interviews and documentation, involving religious leaders, customary elders, officials from the Ministry of Religious Affairs, and members of mixed Malay-Chinese families. The results show that the inheritance system of the Malay-Chinese community is hybrid and flexible, with a distribution pattern that does not fully adhere to any particular legal system. Inheritance practices are based on the principle of distributive justice based on need, where family harmony and deliberation form the basis of social legitimacy. There has also been a shift in gender roles that marks a change in values towards equality between sons and daughters. It was found that the compromise between customary law, religion and the state reflects a form of adaptive coexistence of legal pluralism, where social compliance is determined more by moral values than by formal rules